A comparative analysis of the foreign tax credit system of South Africa, with specific reference to corporate taxpayers and technical service fees - Allanson, Douglas (Department of Finance and Tax, 2022)
The growth in the worldwide services economy combined with an expansion by South African multinational enterprises into the African market has often resulted in increased instances of double taxation for South African corporate taxpayers, as a result of the fact that the majority of the jurisdictions in Africa apply a withholding tax on technical service income paid to nonresidents. The ability to claim relief for the juridical double taxation suffered as a result of the withholding tax applied is governed in South African tax legislation by section 6quat of the Act. This paper analyses section 6quat of the Act with particular reference to the relief available and unavailable to taxpayers for foreign taxes paid in relation to withholding taxes on technical service fee income, in treaty and non-treaty scenarios. The issue of continued double taxation, despite the relief mechanisms of section 6quat, resulting from source issues and the provision of services remotely from South Africa or differing interpretation on the application of Double Taxation Agreements by South Africa and the foreign jurisdictions for example, are also reviewed. South Africa's relief mechanisms are then compared to the relief mechanisms of 5 other jurisdictions (peer nations who export services) to determine if any of these jurisdictions have more advanced ideas for the reduction of juridical double taxation in the context of technical service fees. It is determined in the final analysis that South African taxpayers are not alone with regard to the problem of unrelieved double taxation despite the best efforts of local legislation to provide some form of relief. None of the jurisdictions reviewed have mechanisms in place that provide full relief whilst also protecting the tax base. A number of recommendations are given for ways that South Africa could possibly improve the situation and reduce instances of juridical double taxation. The most obvious being a wide treaty network, with up-to-date treaties, with as many jurisdictions as possible, with a technical services article.